Penerapan Good Governance Dalam Pengelolaan Keuangan Dinas Pekerjaan Umum dan Tata Ruang Kabupaten Buleleng - Dewi, Ni Luh Puja Rosita; Diatmika, I Putu Gede (Vokasi : Jurnal Riset Akuntansi, 2025)
This study aims to evaluate the implementation of good governance principles in financial management at the Department of Public Works and Spatial Planning (DPUTR) of Buleleng Regency. The research focuses on five core principles of good governance: accountability, transparency, participation, effectiveness and efficiency, and rule of law. A qualitative approach was used, employing interviews, observations, and documentation as data collection techniques. The findings indicate that while accountability is implemented through reporting and internal audits, there is a gap in understanding at the technical implementation level. Transparency is still limited due to the lack of accessible public information channels. Public participation in budgeting remains symbolic and procedural. Effectiveness and efficiency are being applied, but outcome-based evaluations are still lacking. Rule enforcement is carried out through SOPs and sanctions, but inconsistencies exist between responses to minor and major violations. The study recommends strengthening human resource capacity, improving public access to information, enhancing meaningful community participation, and ensuring consistent application of reward and punishment systems to achieve better financial governance.